THE INFLUENCE OF TIME-BUDGET PRESSURE ON AUDIT QUALITY OF PUBLIC ACCOUNTANT FIRMS IN DKI JAKARTA - AL ISLAMY, MUHAMMAD HAFIZ (Jurnal Ilmiah Mahasiswa FEB, 2019)
This research is conducted to examine the effect of time-budget pressure andgender differences on audit quality. This research is used primary data that collectedby distributing questionnaires to auditors. The respondent of this research are autditorswho works in public accountant firms in DKI Jakarta. The tool used for data analysiswas multiple linear regressions. The result of this research shows that the time-budgetpressure affects the audit quality. The higher the time-budget pressure that felt by theauditors, the better the audit quality that producedKeywords: Audit, Audit Quality, Time-Budget Pressure, Public Accounting Firms.